Antiracism in Othello sketch comedy, 1967-1999 - Stephen Hamrick (The European Journal of Humour Research, 2022)
Despite Shakespeare’s rejection of comic, racist stereotypes in Othello, minstrel shows offered racist blackface caricatures of slaves and others of African descent that filtered through British Music Hall and Variety to television sketch comedy. Analyses of twenty-five screened appropriations of Othello provide a cultural history of racism for 1967-1999. The article recovers an antiracist tradition overlooked in comedy studies.